Tārīḫ al-qaḍāʾ al-ʿIrāqī fī miʾat ʿām li-taʾsīs ad-daula al-ʿIrāqīya, 1921-2021 - Ḍamad, Ayād Muḥsin; Ġāzī, Munaǧǧid Faiṣal; Zaidān, Fāʾiq (Wizārat aṯ-Ṯaqāfa wa-'s-Siyāḥa wa-'t-Āṯār, Dār aš-Šuʾūn aṯ-Ṯaqāfīya al-ʿĀmma, 2021)
Justice, Administration of ; Iraq; history